2021
DOI: 10.1038/s41467-021-23841-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming differentially affects vegetative and reproductive phenology of tundra plants

Abstract: Rapid climate warming is altering Arctic and alpine tundra ecosystem structure and function, including shifts in plant phenology. While the advancement of green up and flowering are well-documented, it remains unclear whether all phenophases, particularly those later in the season, will shift in unison or respond divergently to warming. Here, we present the largest synthesis to our knowledge of experimental warming effects on tundra plant phenology from the International Tundra Experiment. We examine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 105 publications
(88 reference statements)
4
58
0
Order By: Relevance
“…Interestingly, this suggests an interaction effect of icing and warming magnifying the advancement of phenology found under warming alone (Table S4). Advanced phenology patterns due to warming are consistent with results of simulated summer warming at a circumpolar scale (Collins et al, 2021). Similar to Collins et al (2021), we found a larger shift in reproductive than vegetative phenophases, resulting in a shorter period between leaf emergence and seed dispersal.…”
Section: Negative Effects On Reproduction: a Results Of Trade-offs?supporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, this suggests an interaction effect of icing and warming magnifying the advancement of phenology found under warming alone (Table S4). Advanced phenology patterns due to warming are consistent with results of simulated summer warming at a circumpolar scale (Collins et al, 2021). Similar to Collins et al (2021), we found a larger shift in reproductive than vegetative phenophases, resulting in a shorter period between leaf emergence and seed dispersal.…”
Section: Negative Effects On Reproduction: a Results Of Trade-offs?supporting
confidence: 87%
“…Advanced phenology patterns due to warming are consistent with results of simulated summer warming at a circumpolar scale (Collins et al, 2021). Similar to Collins et al (2021), we found a larger shift in reproductive than vegetative phenophases, resulting in a shorter period between leaf emergence and seed dispersal. This pattern was particularly pronounced under the combined icing and warming treatment, indicating a higher energy investment to reproduction, despite the also high investment to vegetative growth under icing.…”
Section: Negative Effects On Reproduction: a Results Of Trade-offs?supporting
confidence: 87%
See 2 more Smart Citations
“…In a meta-analysis of the international tundra experiment (ITEX), there was generally no treatment effect after four years of OTC treatment on the timing of senescence in various species in up to six different arctic and alpine sites (Arft et al 1999). A more recent meta-analysis including studies with up to 20 years of OTC treatment found a mean delay in senescence across 61 species (Collins et al 2021), which could indicate that there is a lag of several years in the response of autumn senescence to warming. A recent review of ITEX found that the timing of senescence is overall not sensitive to temperature increases across time or space when considering multiple species across the Arctic (Prevéy et al 2017).…”
Section: Passive Autumn Warmingmentioning
confidence: 99%